The novel role of pyrvinium in cancer therapy. Issue 4 (20th June 2017) - Momtazi‐borojeni, Amir A.; Abdollahi, Elham; Ghasemi, Faezeh; Caraglia, Michele; Sahebkar, Amirhossein
Abstract : Pyrvinium pamoate (PP) is a quinoline‐derived cyanine dye which was officially approved by FDA for its anthelmintic properties and therapeutic function against animal‐like protists such as Cryptosporidium parvum and Plasmodium falciparum in the 1950s. In the last 10 years, several studies have shown the novel activity of pyrvinium in tumor therapy. Some investigations have indicated that pyrvinium could delay or inhibit tumor cell proliferation in cancer models including colon, breast, lung and prostate cancer, and some hematological malignancies. In this review, we discuss multiple critical signaling pathways and mechanisms underlying the anticancer effects of PP. In details, pyrvinium acts through the following main mechanisms: (i) energy and autophagy depletion; and (ii) inhibition of Akt and Wnt‐β‐catenin‐dependent pathways. Interestingly, pyrvinium has also shown potent anti‐cancer stem cell activity. The overwhelming insights into the mechanism of anticancer properties of PP can help establishing novel and future anti‐tumor treatment strategies. Abstract : This review presents the mechanisms of anticancer properties of pyrvinium that can help establishing novel and future anti‐tumor treatment strategies.